Obstetric Interventions and Maternal Morbidity Among Women Who Experience Severe Postpartum Hemorrhage During Caesarean Delivery. Issue 5 (October 2017) - Seligman, K.; Ramachandran, B.; Hegde, P.; Riley, E. T.; El-Sayed, Y. Y.; Nelson, L. M.; Butwick, A. J.
Abstract : (Abstracted from Int J Obstet Anesth, 2017;31, 27–36) Postpartum hemorrhage (PPH) causes severe maternal morbidity and mortality in women undergoing cesarean delivery (CD) compared to women undergoing vaginal delivery. The planning and management of PPH varies according to whether PPH occurs during prelabor CD or intrapartum CD.